'Work it out': evaluation of a chronic condition self-management program for urban Aboriginal and Torres Strait Islander people, with or at risk of cardiovascular disease - Kyly Mills; Michelle L. Gatton; Ray Mahoney; Alison Nelson (BMC, 2017)
Abstract Background Chronic diseases disproportionately burden Aboriginal and Torres Strait Islander people in Australia, with cardiovascular (CV) diseases being the greatest contributor. To improve quality of life and life expectancy for people living with CV disease, secondary prevention strategies such as rehabilitation and self-management programs are critical. However, there is no published evidence examining the effect of chronic condition self-management (CCSM) group programs for Aboriginal and Torres Strait Islander people who have, or are at risk of, CV disease specifically. This study evaluates the Work It Out program for its effect on clinical outcome measures in urban Aboriginal and Torres Strait Islander participants with or at risk of CV disease. Methods This study was underpinned by a conceptual framework based on Aboriginal and Torres Strait Islander community control. Participants had at least one diagnosed CV disease, or at least one CV disease risk factor. Short-term changes in clinical outcome measures over (approximately) 12 weeks were evaluated with a quasi-experimental, pre-post test design, using paired t-tests. Factors contributing to positive changes were tested using general linear models. The outcome measures included blood pressure (mmHg), weight (kg), body mass index (kg/m2), waist and hip circumference (cm), waist to hip ratio (waist cm/hip cm) and six minute walk test (6MWT). Results Changes in several clinical outcome measures were detected, either within the entire group (n = 85) or within specific participant sub-groups. Participant's 6MWT distance improved by an average 0.053 km (95% CI: 0.01-0.07 km). The change in distance travelled was influenced by number of social and emotional wellbeing conditions participants presented with. The weight of participants classified with extreme obesity decreased on average by 1.6 kg (95% CI: 0.1-3.0 kg). Participants with high baseline systolic blood pressure demonstrated a mean decrease of 11 mmHg (95% CI: 3.2-18.8 mmHg). Change in blood pressure was influenced by the number of cardiovascular conditions participants experienced. Conclusions Short-term improvements seen in some measures could indicate a trend for improvement in other indicators over the longer term. These results suggest the Work It Out program could be a useful model for cardiovascular rehabilitation and prevention for other urban Aboriginal and Torres Strait Islander populations.